The use of fresh-frozen plasma in England: high levels of inappropriate use in adults and children. - Stanworth, S; Grant-Casey, J; Lowe, D; Laffan, M; New, H; Murphy, M; Allard, S (2011)
BACKGROUND: Fresh-frozen plasma (FFP) is given to patients across a range of clinical settings, frequently in association with abnormalities of standard coagulation tests. STUDY DESIGN AND METHODS: A UK-wide study of FFP transfusion practice was undertaken to characterize the current patterns of administration and to evaluate the contribution of pretransfusion coagulation tests. RESULTS: A total of 4969 FFP transfusions given to patients in 190 hospitals were analyzed, of which 93.3% were in adults and 6.7% in children or infants. FFP transfusions to adults were given most frequently in intensive-treatment or high-dependency units (32%), in operating rooms or recovery (23%), or on medical wards (22%). In adult patients 43% of all FFP transfusions were given in the absence of documented bleeding, as prophylaxis for abnormal coagulation tests or before procedures or surgery. There was wide variation in international normalized ratio (INR) or prothrombin times before FFP administration; in 30.9% of patients where the main reason for transfusion was prophylactic in the absence of bleeding the INR was 1.5 or less. Changes in standard coagulation results after FFP administration were generally very small for adults and children. CONCLUSIONS: This study raises important questions about the clinical benefit of much of current FFP usage. It highlights the pressing need for better studies to inform and evaluate quantitative data for the effect of plasma on standard coagulation tests.